Relationship Between Job Stressor with Job Stress on Salesmen of Household Appliance Trading - Meita Nazla Adila; Mitha Qurrota Ayuni; Tri Martiana; Endang Dwiyanti (Universitas Airlangga, 2023)
Introduction: Salesmen's job is focused on promoting a product directly to consumers. Household appliances are one of the products that is often promoted by salesmen. While carrying out marketing activities, they will always be faced with various job factors that can cause job stress. This research was conducted to analyze the correlation between job stressors and job stress levels among salesmen. Method: This research was observational research with a cross-sectional approach. Both population and samples of this research were 30 salesmen of household appliance trading in Kediri City. The sampling technique used was total sampling. Variables used in this research were job stressor including role conflict, role ambiguity, interpersonal conflict, job uncertainty, total workload, and mental demands with job stress levels. Results: The results showed that most salesmen experienced job stressors either in high, moderate or low category. Most of the salesmen experienced normal job stress level. There is relationship between job stressors consisting of role conflict (0.673), role ambiguity (0.455), interpersonal conflict (0.262), job uncertainty (0.683), total workload (0.526) and mental demands (0.859) with job stress levels on salesmen. Conclusion: An increase in job stressor conditions experienced by salesmen will be followed by an increase in job stress levels, and vice versa. Out of all, mental demands have the strongest relationship to job stress levels on salesmen. So it is necessary to make efforts to suppress existing job stressors so that an increase of job stress levels on salesmen can be prevented.